Cloud Computing Incorporation: Research on Universities in Jordan - Saleem Issa Al Zoubi (International Journal of Advanced Science and Technology, 2020)
Cloud computing integration has been widely recognized and acknowledged in academic education, numerous online university services have implemented cloud computing as it allows students, lecturers, researchers and staff to access data and information from anywhere, at any time without computer equipment requirements or restrictions. The benefits of cloud computing are abundance, which includes enhancing education’s cost-effectiveness, promoting project completion, improving efficiency, and delivering high-quality services. The awareness and highlighting of the most important factors are extracted from ensuring the integration of effective cloud computing into education. The main purpose of this study is therefore to evaluate technological factors that are perceived to affect the integration of cloud computing among Jordanian universities. The primary data were collected using 271 valid and reliable questionnaires distributed by hand to random IT staff in 10 universities. The findings of this research revealed that the technical factors (security and confidentiality, relative advantage and complexity) were correlated with the introduction of cloud computing. The study recommends exploring the need and impact of IT leaders’ strategies for incorporating cloud computing in a different geographic location